THE AGE DISPENSATION FOR MARRIAGE IN SIDOARJO RELIGIOUS COURT: RESEARCH ON 2022 - Priseliya, Khalifa; Ngaisah, Siti (YURIS: Journal of Court and Justice, 2023)
Underage marriage is still prevalent in society. According to the Central Bureau of Statistics in 2017, 25.71% of women aged 20-24 were married when they were less than 18 years old. It means that about 1 out of 4 Indonesian women married at a child's age. The Marriage Law restricts the minimum age for citizens to marry from 21 years old, for both men and women. However, the Marriage Law allows men under 19 years old and women under 16 years old to marry, as long as they receive dispensation from the Religious Court. Therefore, this research is conducted to find out the legal regulation of marriage age dispensation according to Law No. 1/1974 and Law No. 16/2019; and to analyse the actual amount of research on marriage age dispensation at the Sidoarjo Religious Court in 2022. The type of research used is empirical combined with a sociological legal approach which legal sources are obtained from data observation and interviews at the Sidoarjo Religious Court. The amendment in Law No. 16/2019 on the amendment of Law No. 1/1974 on marriage does not provide any change to overcome the surge in marriage dispensation for underage children as happened in the Sidoarjo Religious Court. There are many factors that cause them to apply for marriage dispensation, such as being pregnant out of wedlock with an old womb, the economy, tradition, and a lack of religious understanding.